The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s10755-021-09576-4
|View full text |Cite
|
Sign up to set email alerts
|

The Constructive Overlap: A Study of Multiplex Ties in Students’ Study-Related Networks and Academic Performance

Abstract: This article adds to a growing body of literature on how various types of social relations can work synergistically to promote students' academic success. Students’ study-related social networks affect academic outcome in higher education. The network literature in education generally explores students’ various relations separately, rather than their multiplex relations or when individuals share several relations. This approach risks missing the full complexity of the student experience. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
9
0
2
Order By: Relevance
“…The most stable and resilient ties are those that are multiplex, that is consisting of individuals that are both friends and study partners. In this study, students report that the working network is the most important network for both well-being and outcome of studies, which is consistent with other studies (Fjelkner-Pihl, 2021), but in contrasts to yet other studies claiming that centrality in friendship networks is the most important factor in relation to study outcome (e.g., Rienties & Tempelaar, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most stable and resilient ties are those that are multiplex, that is consisting of individuals that are both friends and study partners. In this study, students report that the working network is the most important network for both well-being and outcome of studies, which is consistent with other studies (Fjelkner-Pihl, 2021), but in contrasts to yet other studies claiming that centrality in friendship networks is the most important factor in relation to study outcome (e.g., Rienties & Tempelaar, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Students often share several types of relations, and these multiplex relations are rewarding for students as they are both expressive and instrumental at the same time as they contribute with both emotional and instrumental support, as well as intellectual engagement and inspiration (Fjelkner-Pihl, 2021;McCabe, 2016). Elmer et al (2020) have shown that if students shared two types of relations (interaction, friendship, informational, or emotional support) the relations were more likely to be maintained during the pandemic.…”
Section: Högre Utbildning 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Social networks in higher education have been found to have a dual connection, as they are both connected to study relationships (instrumental) and friendship (support) (Fjelkner-Pihl, 2022b ; McCabe, 2016 ). The distinction between these is however not always clear as research has shown that friendship ties that evolve into study relationships have been found to be particularly important for students’ success (Stadtfeld et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The distinction between these is however not always clear as research has shown that friendship ties that evolve into study relationships have been found to be particularly important for students’ success (Stadtfeld et al, 2019 ). Research on complex social ties that cover both friendship as well as connections related to studies further indicate that they often overlap (Fjelkner-Pihl, 2022a , 2022b ; McCabe, 2016 ). McCabe ( 2016 ) finds that students’ social networks differ in that some students have a tight network, where the connections are both related to study and friendship, whereas other students compartmentalize these connections or even “sampled” them in individual connections.…”
Section: Literature Reviewmentioning
confidence: 99%